Essays on commodity prices and economic activity in a resource rich country - Paulo, Eugenio Maria (Kansas State University, 2015)
The increase in commodity prices that has taken place in the past decade or so has resulted in renewed interest in the debate about the macroeconomic consequences of such price increase. Previous studies tend to assume that all commodity price shocks are alike and advocate a “one size fit all” policy response by monetary authorities, either by means of contractionary monetary policy to alleviate inflationary pressures or doing nothing, since these shocks are believed to have insignificant economic impact. This dissertation analyses the impact of fluctuations in commodity prices on the South African economy. The first chapter studies the impact of shocks to prices of four commodities on monetary policy variables. Results show that shocks to different commodity prices have different effects on the monetary policy variables, hence rejecting the “one size fits all” policy response by monetary authorities, as some researchers have suggested. Chapter two investigates the sectorial effects of commodity price shocks. The Dutch Disease hypothesis suggests that a boom in the natural resource sector shrinks the manufacturing sector through crowding out and appreciation of the real exchange rate. South Africa is a major exporter of a large number of commodities. Using a structural VAR framework this chapter analyzes the impact of shocks to different commodity prices on the production and employment levels in the manufacturing and mining sectors in South Africa. The results show that the commodity price boom has had a positive impact on both sectors, hence the manufacturing sector did not experience signs of the Dutch disease. Chapter three examines the volatility transmission between commodity prices and nominal exchange rate in South Africa. This chapter uses conditional and realized volatility models to estimate volatility in exchange rate, gold, platinum, oil, palladium and silver prices and then employs Granger-causality, Impulse Response analysis, Variance Decomposition and Ordinary Least Squares to analyze the volatility transmission from the commodity prices to the nominal exchange rate. The results show that there is volatility transmission from commodity prices to the nominal exchange rate, hence knowing the volatility in commodity prices would improve investor’s ability to manage risk in South Africa.
Keywords: Commodity prices; Economic activity; Resource rich country; Dutch Disease hypothesis; South Africa; Volatility transmission exchange rate and commodities; Economics (0501); Economics, Finance (0508); Economic Theory (0511)